Recognizing Fault Structures and Studying the Evolution of Karst Sources Using Ground Penetrating Radar (Case Study: Kermanshah Province) - Amjad Maleki; Mohsen Ovaisy (جغرافیا و پایداری محیط)
In karst regions, the main goal of geophysical method is to study carbonate stone, which are not directly visible. By geophysical method, it is possible to gain some valuable information about amount of stone and describe horizons containing inconsistencies which are of great interests in karst studies. The region under study located in zagros producing zone have been built out of carbonate constitutes. Karst springs of kermanshah play an important role in providing the water for kermanshah province, because of this importance, geophysical operations have been done to recognize the role of earth structure (fractions) in making karset springs. GPR is one of important methods in recognizing the surface structure of earth. In this study, using GPR geophysical deeds have been done in two springs of sarab yavari (zone according to zagros) and sarab niloofar (unfair zone of zagros). Using 100 MHz antenna, the some related information was obtained , and The surface fraction and in consistent zones have been studied, these studies show that sarab yavari spring which is located in zagros fraction has more solution phenomena, but sarab niloofar spring which is located in inconsistent zagros zone has less solution phenomena . the results of this study show that GPR is able to recognize karst springs closely and the obtained results are more acceptable and reliable.